Comparison of the Effect of Propofol and Sevoflurane Anaesthesia on Acute and Chronic Postoperative Pain after Hysterectomy. Issue 3 (May 2014) - Ogurlu, M.; Sari, S.; Küçük, M.; Bakiş, M.; Uğur, B.; Eshraghi, Y. E.; Galimberti, F.; Turan, A.
There is some evidence that propofol may reduce acute postoperative pain; however, the results are inconsistent. Furthermore, there is a paucity of information about the type of anaesthesia and chronic pain. This study was designed to evaluate the hypothesis that propofol reduces acute and chronic postoperative pain compared with sevoflurane. In a randomised, prospective, double-blind trial, we assigned 80 patients having open total abdominal hysterectomy surgery to anaesthesia with either sevoflurane or propofol. Anaesthesia was titrated to clinical needs and bispectral index values to between 40 and 60. Postoperative pain was managed with pethidine and diclofenac. Acute postoperative pain for 24 hours and chronic postoperative pain at one and three months after surgery were evaluated. The Hospital Anxiety and Depression Scale was used to evaluate patient anxiety and depression after one and three months. There were no significant differences between the groups for opioid consumption or opioid-induced side-effects. Pain scores in the first four hours were significantly higher in the sevoflurane group. Persistent surgical pain was observed less frequently (7 out of 40 patients in the propofol group and 21 out of 40 in the sevoflurane group at three months post-surgery, P <0.01) and pain scores were lower at one and three months in the propofol group (0.78±0.55 versus 2.23±0.73 for the sevoflurane group at three months post-surgery, P <0.01). Anxiety and depression scores were significantly lower in the propofol group at three months. In this study, general anaesthesia with propofol was associated with reduced early acute postoperative and persistent pain, compared to sevoflurane-based anaesthesia, among patients undergoing open abdominal hysterectomy.